Volumetric Magnetic Resonance Imaging Investigation of the Pituitary in Patients with Vaginismus - Atmaca, Murad; Gürok, Mehmet Gürkan; Tabara, Muhammed Fatih; Mermi, Osman; Korkmaz, Sevda; Baykara, Sema; Yıldırım, Hanefi (Istanbul Universitesi, 2025)
Objective: Many previous studies have reported decreased pituitary volume in various anxiety disorders compared to healthy controls. In this context, this study was conducted with the hypothesis that pituitary volume is reduced in this patient group as in other anxiety disorders. Methods: Ten women with vaginismus and 10 healthy controls were included in the study. Structural magnetic resonance imaging and volume measurements of the participants were performed in the radiology department. Results: The mean pituitary volume of women with vaginismus was found to be significantly decreased compared to healthy controls. Conclusion: The present findings suggest that vaginismus may be closely related to anxiety-related conditions involving at least the pituitary gland. © Author(s).
Keywords: Gland volume; MRI; neuroimaging; pituitary; vaginismus